Faktor-Faktor yang Mempengaruhi Pendapatan Petani Jeruk pada Desa Gunung Bau Kecamatan Kintamani Kabupaten Bangli - Alitawan, Anak Agung Irfan; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 5, Mei 2017 (pp. 677 - 919), 2017)
Agriculture sector is a sector that is very important role in the economy of most of the countries that are developing. Agricultural development needs to get better attention, despite the priority at the discretion of industrialization had been dropped, but the agricultural sector has the ability to generate increased revenue. The primary data used in this research is data collected by a structured interview. Secondary data used in this study was obtained from the BPS Provincial Office of Agriculture and Village Office Gunung Bau. Methods of data analysis used in this study were multiple linear regression. The study states that the land area of ??positive and significant influence simultaneously and partially on the income, the amount of production has positive effect simultaneously and partially on the income, and the cost of farming positive and significant effect simultaneously on the income, while the cost of farming has negative and significant partial on income. This shows that increasing land area, the amount of production and the cost of farming, the farmers' income will also increase. To increase the income can be done by providing assistance such as seeds, fertilizers, pesticides and agricultural equipment from the government in order to increase citrus production and maximum quality so as to increase farmers' income.
Keywords: luas lahan, produksi, biaya usaha tani, pendapatan